Culturally responsive pedagogy in practice: Integrating Thai local culture into an intensive English primary - Khoirun Nisa'; Nur Lailatul Mufidah; Wassana Aeadsongkram B.A; Lilik Huriyah (Journal of English Language and Pedagogy, 2025)
The paper reviews the application of culturally responsive pedagogy as a means of inserting the element of Thai local culture solely in the Primary Intensive English Program (IEP) in Narathiwat, Thailand. The qualitative descriptive design was used, and data were gathered by using classroom observations, semi-structured interviews and documentation. The fieldwork took place during the months of July and comprised of three classroom observations, and three classes of primary students, using various materials and various students. The participants for interview were three IEP teachers and three primary students who were chosen according to teacher suggestions to guarantee direct interaction with culturally encoded instructions activities. Findings indicate that the Thai cultural aspects, including local narratives, everyday settings, local words, and routines based on the cultural context, were integrated by the teachers in an attempt to promote understanding and involvement. The research comes to the conclusion that the implementation of the Thai-only cultural content by means of culturally responsive pedagogy enhances student engagement, reinforces the contextual knowledge, and provides a feasible way to apply the model to EFL classrooms in the Southeast Asian cultural settings.